HUBUNGAN STATUS AKLIMATISASI DAN EFEK HEAT STRESS PADA PEDAGANG KAKI LIMA DI DEPAN POLINES (POLITEKNIK NEGERI SEMARANG) JL. PROF. H. SOEDARTO, SH, TEMBALANG, SEMARANG - Budhiasih, Rizka Tamimi; Widjasena, Baju; Jayanti, Siswi (Jurnal Kesehatan Masyarakat (e-Journal), 2015)
According to Badan Meteorologi Klimatologi dan Geofisika estimation, in 2014 temperature in Semarang was around 23 – 36°C. High work temperature may cause heat stress effect, such as: heat rash, heat cramps, heat syncope, heat exhaustion, and heat stroke. In order to avoid heat stress effect, the workers have to pay attention for these factors: acclimatization status, mineral intake, work load, and personal protective equipment. Tempo newspaper explained that in October 2014 was the highest climate record on Semarang since 1972, it was 36°C. The purpose of this research is to know the correlation between acclimatization status and heat stress effect on street vendors located in front of Politeknik Negeri Semarang, Jl. Prof. H. Soedarto, SH, Tembalang, Semarang. This research use quantitative method with cross sectional approach. The populations on this research are 38 people who work as street vendors and total samples that taken by using inclusion and exclusion criteria are 35 people. Chi Square test result shows that there were no correlation between acclimatization status and heat stress effect (p = 0,127), no correlation between mineral intake and heat stress effect (p = 0,966), no correlation between personal protective equipment and heat stress effect (p = 0,508). Rank Spearman test result shows that there was no correlation between work load and heat stress effect (p = 0,265 and r = 0,193). The researcher suggest, the workers can overcome the heat stress effect by drink 2,5 liters water every day. Besides that, the workers can use personal protective equipment by using a cotton shirt to absorb the sweat maximally and using a head cover to protect the skin head from the sunlight.